application PENERAPAN AKUNTANSI ZAKAT DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA ZAKAT, INFAK DAN SEDEKAH PADA BAZNAS PROPINSI BALI - Hasibuan, Henny Triyana (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
This study aims to analyze application of zakat accounting in Baznas Bali Province in increasing transparency and accountability in management of zakat, infak and sedekah (zis) funds. This research is a qualitative research. The results of this study indicate that Bali Provincial Baznas have complied with PSAK No. 109. Receipts of zakat, donations and alms are assessed when cash or other assets are received. Accepted zakat, recognized as amil and non amil funds, determination of the percentage of zakat funds received for each mustahiq based on sharia principles is 12.5%. Distribution of zakat, infak and sedekah funds as a deduction from zakat, alms and alms funds. The components Baznas Bali's financial statements are statement of financial position, report on changes in funds, reporting on cash flows and notes to financial statements. The absence an asset management report in accordance with PSAK 109 is due to Baznas Bali Province not having fixed assets, all assets are in form of current assets. Accountability is reflected in financial statements that have been audited by independent auditors, while transparency of financial statements is contained in reports in the form of bulletins that are published periodically. The implication results of research is expected to be financial statements Baznas of Province of Bali which can be an example in management of infaq and alms funds throughout Indonesia. It is recommended for further research to be able to broaden scope of regional research throughout Indonesia, so that research results can be generalized nationally.